Child brides [Çocuk gelinler] - (:unkn) unknown (My University, 2013)
Early marriage, defined as marriage before 18 years of age, has been associated with a variety of negative outcomes such as low education status due to dropping out of school, teenage pregnancies, increased maternal and infant mortality and poverty. The negative outcomes have the potential to affect not only the individuals but also their children and the community. This review article aimed to investigate the issue of child marriage in our country and around the globe, and to evaluate the recommendations for the prevention of early marriage. Poverty and low education status are the most important factors contributing to child marriage. Promoting strategies focusing on girls' education and targeting social inequalities seem to be the most effective solutions to prevent child marriage.
Keywords: Child brides; Early marriage; Teenage pregnancy